Avaliação da qualidade da água proveniente de estações de tratamento de água salobra na zona rural do município de Mossoró, RN - Cosme, Christiano Rebouças (Universidade Federal Rural do Semi-Árido, 2011)
In Brazil, mainly in the semiarid region, a major challenge is to promote the water supply to households in rural areas. Groundwater is identified as a viable alternative to ensure the access of rural communities in the northeast to water from public investment in drilling wells. However, these water sources in most cases have use restrictions for human consumption, because they present problems of salinity. The technology of reverse osmosis has been widely used for treatment of brackish water, with successful experiences in most locations where units have been deployed in water treatment by desalination. Many rural communities in Mossoró, RN, are supplied with water from the aquifer Jandaíra, high salt concentration, which is treated in desalination plants, allowing its use for human consumption. In these communities, the reject brine of the process of desalination is not receiving any treatment or proper disposal, being dumped straight into the ground and, when used in irrigation of crops there are no scientific-technical reasons for their use, causing problems of soil salinization. Due to the impacts caused by the use of brackish or reject brine for irrigation in the soil, to enable their use should always adopt some special practices of water management and soil for salinity control. As the majority of crops grown in the region classified as sensitive to moderately sensitive to salinity, there is the need to better characterize these waters, to establish the appropriate management of plants, soil and irrigation systems. As the majority of crops grown in the region are classified as sensitive to moderately sensitive to salinity, there is the need to better characterize these waters, to establish the appropriate management of plants, soil and irrigation systems. Thus, this study aimed to evaluate the quality of water for irrigation in rural communities of Mossoró, supplied with brackish water from tube wells equipped with desalination, providing this information as a tool to aid the proper management and use of these waters irrigation. 30 rural communities were selected to perform the collection of samples of water from the waste generated in the desalination, purified and in its natural form (brackish water of the well). In the collected samples were determined at electric conductivity (ECw), pH and concentrations of Na+, Ca2+, K+, Cl-, HCO3 - e CO3 2-, in addition, the sodium adsorption ratio (SAR). The Analyses of water samples were interpreted as to risk of salinity, sodicity, toxicity of ions and other quality parameters. The results show that water of the wells rural communities studied, have restrictions to their use in agriculture, as to risks of salinity and sodicity of the soil, especially the waters of the communities: São Romão, Boa Fé and Pau Branco. the reject brine of the desalination have high concentrations of salts, especially in communities of Boa Fé and Puxa Boi, compromising their use for irrigation, and, the desalinated water, although they have low concentrations of salts have restrictions on the problems of infiltration into the soil, if by chance, are employed in irrigation.
Evaluation of water quality from treatment plants of brackish water in rural zone of the Mossoró, RN
Keywords: Salinity; Brackish waters; Irrigation; Salinidade; Águas salobras; Irrigação; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE SOLO E AGUA::IRRIGACAO E DRENAGEM